2009
DOI: 10.1177/0734242x07085754
|View full text |Cite
|
Sign up to set email alerts
|

Waste-handling practices at red meat abattoirs in South Africa

Abstract: Abattoir waste disposal must be carefully managed because the wastes can be a source of food-borne diseases (Nemerow & Dasgupta Industrial and Hazardous Waste Treatment, p. 284, Van Nostrand Reinhold, New York, 1991; Bradshaw et al. The Treatment and Handling of Wastes, p. 183, The Royal Society, Chapman & Hall, London, 1992). Disposal of food that has been condemned because it is known to be diseased is of particular concern, and this paper looks at current disposal methods for such waste in the light of new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Abattoir is one of the food industries that contribute to the problem of possible food-borne diseases and health hazards associated with food unless the principles of food-borne hygiene practices are implemented [24]. The current study showed that there was no clear division of slaughtering process: stunning, bleeding, skinning, evisceration, hanging, and cutting/deboning.…”
Section: Discussionmentioning
confidence: 76%
“…Abattoir is one of the food industries that contribute to the problem of possible food-borne diseases and health hazards associated with food unless the principles of food-borne hygiene practices are implemented [24]. The current study showed that there was no clear division of slaughtering process: stunning, bleeding, skinning, evisceration, hanging, and cutting/deboning.…”
Section: Discussionmentioning
confidence: 76%
“…Approximately 50-54% of each cow, 52% of each sheep or goat, 60-62% of each pig, 68-72% of each chicken, and 78% of each turkey end up as meat consumed by human beings with the remainder becoming waste after processing [7]. Moreover, of abattoir waste, the volume of wastewater from abattoirs is 70-75% of the abattoir water that contributes to a high organic load as well as a considerable amount of suspended material in the waste [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this study there was significant association between abattoir effluents and diseases affecting abattoir neighbouring community (Table 3 and 4). According to [7] reported that abattoir effluents contain a lot of disease causing organisms. Similarly medical expert were reported to have associated some diseases with abattoir activities which include: pneumonia, diarrhoea, typhoid fever, asthma, wool sorter diseases, respiratory and chest diseases [1].…”
Section: Univariable Analysis Of Factors Associated With Abattoir Activities On Residential Neighbourhood's Healthmentioning
confidence: 99%